An Unusual Case of Swelling of Tuberculosis of Elbow and Forearm: A Case Report - Agrawal, Siddharth (J Orthop Case Rep, 2020)
INTRODUCTION: Mycobacterial infection of the upper extremities is rare with elbow joint being most frequently affected accounting for 2– to 5 % of all skeletal localizations. Diagnosis is of paramount importance in tuberculosis of elbow because delay in analysis could prime to serious difficulties. CASE PRESENTATION: We describe a rare presentation of a 38- year- old male with tuberculosis of elbow joint. Massive swelling of forearm with subcutaneous collection without any significant involvement of forearm muscles has rarely been reported. This case will be a significant addition to literature with respect to clinical presentation of elbow tuberculosis. CONCLUSION: Tuberculosis of elbow along with that of a forearm is rare and surgical intervention can lead to better outcomes in these patients.